2017
DOI: 10.1002/anie.201704793
|View full text |Cite
|
Sign up to set email alerts
|

An Activatable Photosensitizer Targeted to γ‐Glutamyltranspeptidase

Abstract: We adopted a spirocyclization-based strategy to design γ-glutamyl hydroxymethyl selenorhodamine green (gGlu-HMSeR) as a photo-inactive compound that would be specifically cleaved by the tumor-associated enzyme γ-glutamyltranspeptidase (GGT) to generate the potent photosensitizer HMSeR. gGlu-HMSeR has a spirocyclic structure and is colorless and does not show marked phototoxicity toward low-GGT-expressing cells or normal tissues upon irradiation with visible light. In contrast, HMSeR predominantly takes an open… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(73 citation statements)
references
References 19 publications
0
73
0
Order By: Relevance
“…Thirteen years later, Se‐rhodamine dye 87 (λ em =557 nm) was again exploited. The Urano group adopted a spirocyclization‐based strategy to design a photosensitizer (gGlu‐HMSeR) that was specifically activated by the tumor‐associated enzyme γ‐glutamyltranspeptidase (GGT); upon activation, a potent photosensitizer (HMSeR) was released in order to selectively ablate implanted tumor spheroids without damage to the healthy tissues (Figure ) . Recently, Hanaoka's group also employed 87 to design a Se‐rhodamine‐based hypoxia‐sensitive fluorescence probe.…”
Section: Substitution Of the Oxygen Atom Of Xanthene Rhodamine Dyes Wmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirteen years later, Se‐rhodamine dye 87 (λ em =557 nm) was again exploited. The Urano group adopted a spirocyclization‐based strategy to design a photosensitizer (gGlu‐HMSeR) that was specifically activated by the tumor‐associated enzyme γ‐glutamyltranspeptidase (GGT); upon activation, a potent photosensitizer (HMSeR) was released in order to selectively ablate implanted tumor spheroids without damage to the healthy tissues (Figure ) . Recently, Hanaoka's group also employed 87 to design a Se‐rhodamine‐based hypoxia‐sensitive fluorescence probe.…”
Section: Substitution Of the Oxygen Atom Of Xanthene Rhodamine Dyes Wmentioning
confidence: 99%
“…TheU rano group adopted as pirocyclization-based strategy to design ap hotosensitizer (gGlu-HMSeR) that was specifically activated by the tumor-associated enzyme g-glutamyltranspeptidase (GGT);u pon activation, ap otent photosensitizer (HMSeR) was released in order to selectively ablate implanted tumor spheroids without damage to the healthy tissues ( Figure 8). [50] Recently,Hanaokasgroup also employed 87 to design aSerhodamine-based hypoxia-sensitive fluorescence probe.T his was achieved by introducing an azo moiety into the conjugated system of rhodamine fluorophores. [51] When Naganos group studied Si-rhodamine fluorophores,t hey also investigated Ge-substituted rhodamine dyes 88 (l em = 649 nm) and Te -substituted rhodamine dyes 89-90.F luorophore 89 has al ow quantum yield (< 0.001) but can be oxidized to fluorescent Te O-rhodamines 90 (l em = 686 nm) with ah igher quantum yield of 0.18.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Recently, Urano et al. extended the strategy to develop the first GGT‐activatable photosensitizer ( 6 ) through using hydroxymethyl selenorhodamine green (HMSeR) instead of HMRG . It was found that the photodynamic activity of 6 could be rapidly activated by GGT‐overexpressing cancer cells, triggering tumor‐specific phototoxicity (Figure B).…”
Section: Activatable Fluorescence Probes For Ggtmentioning
confidence: 99%
“…Lastly, theranostic prodrugs providing both real‐time hNQO1 activity monitoring and anticancer drug release in a single molecule have also been reported . However, despite the diverse set of probes currently exploiting hNQO1, to date, there are no reports of an hNQO1‐targeted optical therapeutic that can be used for PDT . With this in mind, we sought out to develop the first activatable PS (aPS) targeting hNQO1.…”
Section: Introductionmentioning
confidence: 99%
“…[31,32] However,d espite the diverse seto fp robesc urrently exploitingh NQO1, to date, there are no reportso fa nh NQO1targeted optical therapeutic that can be used for PDT. [33][34][35][36][37][38] With this in mind, we sought out to develop the first activatable PS (aPS)t argeting hNQO1.…”
Section: Introductionmentioning
confidence: 99%